Analisis Pengaruh Tegangan Tidak Seimbang pada Kinerja Motor Induksi menggunakan Metode Transformasi Direct Quadrature - Paulus Setiawan (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2019)
Induction motors are one type of electric motors that work based on electromagnetic induction. The problem that often arises lately is the occurrence of voltage imbalances. Unbalanced voltage is a voltage value that is not the same in a three-phase voltage system contained in the electrical power system. On the basis of these problems, it is necessary to conduct research that can analyze the dynamics of the performance of an induction motor. Dynamic analysis is done by modeling a three-phase induction motor using an arbitrary reference frame with the direct qudrature transformation method in Matlab/Simulink. In studies with voltage imbalances up to 5%, electromagnetic torque has decreased by 2.89% to 13.83% and stator current in one phase has increased by 29.1% to 245.8%.